An evolutionary game study of environmental regulation strategies for marine ecological governance in China - Gao, Lehua; Yan, An; Yin, Qiaorong (Frontiers in Marine Science, 2022)
The choice of environmental regulation strategy for marine ecological pollution governance is a vital issue for China to promote collaborative marine ecological management. Firstly, we establish a three-party evolutionary game model of the central government, local government, and marine enterprises from the environmental policy perspective. Secondly, numerical simulations are used to investigate the differences in the effects of incentive-based and penalty-based policies of the central and local governments on local governments and marine enterprises, respectively. Finally, we introduce a reputation loss model of public participation to explore the game strategy choices of the three parties under public participation. The study finds that: (1) Local governments are more sensitive to the central government's punishment policies than marine enterprises. (2) Although local government subsidies for enterprises can increase their probability of managing marine ecology, they can also lead to a decrease in the willingness of local governments to implement. Moreover, the local government's policy of punishing enterprises is more direct and effective than the central government. (3) Although local governments' subsidies for enterprises can increase their probability of managing marine ecology, they can also decrease their willingness to implement. (4) Public participation can more quickly promote the active governance of marine enterprises.